The Motley Fool UK Investment Guide - Berger, David (Macmillan Publishers Ltd, 2000)
In this no-nonsense guide, the Motley Fools show you how to invest your money wisely for a profitable future. If your idea of investment begins and ends with a savings account at a building society, then this is the book for you. Using practical examples and with their usual off-the-wall style, the Fools cut through financial jargon and take you through the basics of investing.
Keywords: Investment Guide; Non Fiction